What’s your sign? Personal Name Signs in Mexican Sign Language - Cruz-Aldrete, Miroslava; González Muciño, Hann Bastian (Onomástica desde América Latina, 2022)
The use of a name/nickname/SIGN within the deaf community plays an important role, since it is a sign that identifies not only the deaf members of the same community, but also the listeners who are related to it. This sign is given by one of the members of the deaf community and implies both acceptance and identity within it. The creation of a personal sign in Mexican Sign Language responds to different ways of forming the name/nickname/sign that vary for each person. This research presents, first, the relevance of the proper name as a social element. Subsequently, the background on the study of personal signs in other sign languages. Finally, based on interviews with members of the deaf community, the three processes found for the formation of personal signs in Mexican Sign Language are shown: the assignment of signs by outstanding physical or behavioral traits; signs that have been inherited or that they share articulatory features in the family; and name sign change.